Li-Fi for a Digital Urban Infrastructure: A Novel Technology for the Smart City - Iannucci, Corrado; Pini, Fabrizio (TeMA - Journal of Land Use, Mobility and Environment, 2014)
The process of “building a smart city” implies that the way a urban area provides its traditional functions be properly re-designed, in order to meet the often conflicting requirements of furthering the economical development and of improving the quality of the life. ICT can make available methodologies and tools able to support such process, as far as the new solutions are carried out within a global vision of the task to be carried out i.e. within a system approach. In such context, even traditional infrastructures as the streetlamp system of a city can reveal interesting opportunities, when coupled with updated technologies. Here, the potential benefits of moving to the LED technologies are presented. The relevance of Li-Fi technology is pinpointed. in relation to the ability of efficiently install wireless links for data transfer without increasing (or also reducing) the microwave background in a urban area.  Also the data collection can be improved leveraging upon the already installed streetlamps: the ever increasing amount of sensors (required for many functions, from street security to environment protection) can be deployed without further waste of urban 3D space.